Textual argumentation of the Shia-Sunni Adhān: a call to defending sectarian craving for Islamic authority in Indonesia and Iran - DH, Achmad Zuhdi; Said, Imam Ghazali (Indonesian Journal of Islam and Muslim Societies, 2024)
The basis of the adhān should be the mutawatir hadith that resulted in consensus because the call to prayer sounds five times a day and night in public hearings. In reality, the call to prayer has been the object of controversy between Shia and Sunni Muslims. This includes its authentic origins, various phrases, and underlying arguments. This article offers theoretical significance to understand sectarian discourse and practical insights to stimulate Shia-Sunni harmony by using Appleby’s theory of the ambivalence of the sacred. The research begins by building a theoretical framework to understand sectarian variations, followed by an accessible literature review reinforced with related scholarly articles, historical records, and other Islamic texts. This, in turn, entails a comparative analysis to examine the differences in wording and content in the traditional call to prayer in the Shia-Sunni community. This study finds that the Shia-Sunni conflict over the Adhan can be a door to enlightenment to eliminate prejudice and tension between the two largest Islamic schools, Sunni-Shia, by acknowledging, realizing, respecting, and appreciating each other’s differences